2016
DOI: 10.1111/jog.13017
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous cesarean scar pregnancies managed by suction curettage alone or in combination with other therapeutic procedures: A series of 33 cases and analysis of complication profile

Abstract: In appropriate CSP cases, TAUS-guided suction curettage appears to be a reliable treatment option with acceptable success rates and similar complication profile to other therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In this observational study, only one patient (2.3%) manifested uterine rupture after curettage and 4 (9%) patients revealed persistent bleeding during the procedure. Although the rate of uterine ruptures was consistent with the literature 15 , the persistent bleeding rate was lower in our study compared with the literature 33 . This lower rate may have resulted from appropriate patient selection, surgical experience or the surgical technique we performed.…”
Section: Discussionsupporting
confidence: 91%
“…In this observational study, only one patient (2.3%) manifested uterine rupture after curettage and 4 (9%) patients revealed persistent bleeding during the procedure. Although the rate of uterine ruptures was consistent with the literature 15 , the persistent bleeding rate was lower in our study compared with the literature 33 . This lower rate may have resulted from appropriate patient selection, surgical experience or the surgical technique we performed.…”
Section: Discussionsupporting
confidence: 91%
“…Our multiple logistic regression analysis showed an association between the success rate and the primary treatment options. Treatment by uterine curettage showed a success rate of 48% [reviewed in ( 14 )] and it should be performed when the serum β-hCG level is <50 IU/L without blood flow velocity ( 15 ) or in type 1 caesarean scar pregnancy ( 16 ). In our current study, we found that the overall success rate by uterine curettage was 70% and there was no difference in the levels of β-hCG in cases who received three different options of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Özkan Özdamar et al demonstrated that in appropriate CSP cases, ultrasound-guided suction curettage appears to be a reliable treatment option. [ 12 ]. Jurkovic D. also considered suction curettage as an effective method for the treatment of CSP which was associated with a lower risk of blood transfusion and hysterectomy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%